Cell signaling by vitamin E - Azzi, Angelo (Henry Stewart Talks, 2007)
Vitamin E or tocopherol's physiological molecular mechanism helps to understand protection against disease, Not an antioxidant or free radical quencher, they perform cell signaling by affecting protein phosphorylation (for instance protein kinase C and PI3 kinase), They can be phosphorylated to more potent species, the tocopheryl phosphates, Tocopheryl phosphates protect, in animal models against atherosclerosis
Reviewed at 2017/10/21